Outcome of umbilical vs. epigastric port retrieval of gall bladder in laparoscopic cholecystectomy - Shrestha, Alok; Chandra Neupane, Harish; Narayan Shah, Jay; Kumar Mishra, Rohit; Raya, Akash; Kumar Yadav, Basant (Journal of Chitwan Medical College, 2025)
Introduction: Postoperative pain remains a significant concern, particularly at port sites. This study aims to compare efficacy of umbilical and epigastric ports in postoperative pain. Method: A comparative study was conducted in the department of surgery at Chitwan Medical College Teaching Hospital from Sep 2024 to Feb 2025. The study comprised patients who had been diagnosed with symptomatic cholelithiasis and excluded emergency laparoscopic cholecystectomy for perforated gallbladder, radical laparoscopic cholecystectomy for gallbladder carcinoma, anticipatory extended cholecystectomy for thick-walled gallbladder, laparoscopic converted to open. The ethical approval was obtained. Total of 86 patients were included in the study and were divided into umbilical and epigastric group equally. Lottery method was used for randomization for first case and alternatively allocated. Visual Analogue Scale (VAS) scoring was done, requirement of rescue analgesic was recorded and a dose required was calculated. Chi-square test was used to compare categorical data and independent student t test was used to compare continuous data. Result: A significant difference was seen in VAS score at 16 and 24 hours (p=0.005, p=0.01 respectively) with high pain complaint among epigastric group. Total VAS score was higher in epigastric group (18.19±4.636) which was statistically significant. More dose of rescue analgesia was required in epigastric group when compared with umbilical group which was statistically significant. Conclusion: This study highlights the significant advantages of umbilical port retrieval over epigastric port retrieval in laparoscopic cholecystectomy, particularly in terms of postoperative pain and analgesia use.